Scanning Angle Magnification with Compact Reflective Optics for Light Detection and Ranging - Cheng-Ta Mu; Po-Cheng Chang; Cheng-Huan Chen (Photonics, 2022)
The function of lidar requests a large scanning angle for a wide field of view and a well calibrated collimation of the laser beam for distant sensing. Besides meeting the required functionality, the compact form factor of the whole optical system is also highly desirable for the ease of being installed in mobile systems. In corresponding to the currently developed phase array laser which can achieve beam scanning without mechanical movement but still with a small scanning angle, a compact optics consisting of only two reflective surfaces has been proposed to magnify the scanning angle of a laser beam up to seven times while keeping the divergence of the laser beam smaller than 8 mrad for some short distance applications. The prototype has been prepared and evaluated with the expected performance.